Single dose phenobarbitone prevents convulsions in cerebral malaria. - White, N; Looareesuwan, S; Phillips, R; Chanthavanich, P; Warrell, D (1988)
48 patients over 6 years of age with strictly defined cerebral malaria were randomised to receive either a single intramuscular injection of phenobarbitone (3.5 mg/kg) or placebo in a double-blind, placebo-controlled study. Phenobarbitone significantly reduced the incidence of subsequent convulsions from 54% to 12.5%, without adverse effects. A single intramuscular injection of phenobarbitone is a simple, cheap, and effective method for prevention of convulsions in cerebral malaria.